Preparing Future Science Teachers: An Analysis of Scientific Literacy and Critical Thinking Skills of Biology Education Students - Samsuri, Taufik; Arnyana, lda Bagus Putu; Suma, Ketut; Suja, I Wayan; Santosa, Made Hery; Widiana, I Wayan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aims to analyze the profiles of scientific literacy and critical thinking skills (CTS) of prospective teachers in the Biology Education Program at Universitas Pendidikan Mandalika, and to identify the gap between current instructional practices and the conditions needed to more effectively support these competencies. A concurrent triangulation mixed-methods design was employed, integrating a scientific literacy test, a CTS test based on the Ennis framework, classroom observations, document analysis of syllabi and lesson plans, perception questionnaires, and semi-structured interviews. Participants comprised 64 undergraduate students from the third, fifth, and seventh semesters, selected through purposive sampling. The results indicate that students’ scientific literacy was at a moderate level (M = 67.03; SD = 7.97), as was their critical thinking (M = 65.23), with the higher-order indicators of evaluation and inference identified as the weakest dimensions. One-way ANOVA revealed statistically significant differences across semester cohorts for both scientific literacy (F = 4.273; p = 0.018; η² = 0.12) and CTS (F = 5.012; p = 0.010; η² = 0.14), with post-hoc analysis localizing these differences specifically between the third and seventh semester cohorts. Pearson correlation analysis showed a moderate-to-strong positive relationship between scientific literacy and CTS (r = 0.612; 95% CI [0.45, 0.74]; p < 0.01). Qualitative findings reveal that learning remains predominantly lecturer-centered, with limited integration of inquiry-based activities and socio-scientific issues and minimal evidence-based argumentation. Triangulation indicates that instructional design factors, rather than students’ inherent capacity alone, appear to be a primary contributor to the observed competency gap. These findings underscore the need to strengthen instructional design—particularly through the integration of inquiry-based learning, socio-scientific issue (SSI) frameworks, and evidence-based argumentation—to develop 21st-century competencies among prospective science teachers.